Diatomological And Physico-Chemical Study Of Galta Kund, Jaipur, Rajasthan (India) - RASHMI PAREEK,; GAJENDRA PAL SINGH, (International Journal of Pharma and Bio Sciences, 2012)
Diatoms are one of the most common types of phytoplankton which contributes to a substantial portion of primary production in many lakes and oceans. In the Present study, the diatomological investigation has been carried out from Oct 2009 to Sep 2010 on the water of Galta Kund in relation to selected physicochemical parameters. During the study period, about 24 species of diatoms were analyzed quantitatively and qualitatively. Water analysis is done for selected physicochemical parameters like Biological oxygen demand (BOD), Chemical oxygen demand (COD), Dissolved oxygen (DO), Total dissolved solids (TDS), Rainfall, Relative Humidity, pH and Temperature. The results indicate that the density of diatom species was influenced by physical and chemical factors of the environment.